Diagnostic Illustrations: Integration and Changes of Western Transmission of Traditional Chinese Medicine Pulse Diagnosis Diagrams - Jie MA; Zhiheng GUO (Chinese Medicine and Culture)
Abstract. Throughout the long development of the Silk Road, traditional medical techniques from various countries have continued to intersect and integrate, and traditional Chinese medicine (TCM) has also been transmitted to Eurasia via the Silk Road. In the process of TCM knowledge dissemination, the tangible pulse diagnosis diagrams (脉诊图) have been collected in works such as Tānksūqnāmah (《伊利汗中国科技珍宝书》 Ilkhanate Chinese Science and Technology Treasure Book), Specimen Medicinae Sinicae (《中医指南》 A Guide to Traditional Chinese Medicine), and Die Chinesische Medizin (《中华医学》 Chinese Medicine), and has become an important carrier and cultural symbol of pulse diagnostics, integrating into Eurasian medicine. The dissemination of TCM pulse diagnosis and the pulse diagnosis diagrams are closely related to Nan Jing (《难经》 The Classic of Difficult Issues) and the pulse studies of the Jin dynasty medical scholar, Wang Shuhe (王叔和). The study found that the pulse diagnosis diagrams had distinct characteristics in its transmission to the West in different eras, and they are analyzed from the perspectives of “communicators (translators)”, “translation characteristics”, “cultural background”, “inheritance system”, revealing multiple integrations and transformations of ancient TCM pulse diagnosis diagrams in the East-West exchange and mutual learning. The pulse diagnosis diagrams have gradually become a symbol of TCM diagnostic methods, forming an inseparable link between TCM and pulse diagnosis in the minds of scholars and the public in the East and West.